Dealing with Data Pocket Primer. - Campesato, Oswald (Computing, 2022)
As part of the best-selling Pocket Primer series, this book is designed to introduce the reader to the basic concepts of managing data using a variety of computer languages and applications. It is intended to be a fast-paced introduction to some basic features of data management and covers statistical concepts, data-related techniques, features of Pandas, RDBMS, SQL, NLP topics, Matplotlib, and data visualization. Companion files with source code and color figures are available. FEATURES:Covers Pandas, RDBMS, NLP, data cleaning, SQL, and data visualizationIntroduces probability and statistical conceptsFeatures numerous code samples throughout Includes companion files with source code and figures.